The degree of parental awareness of using means of physical rehabilitation on the frequently ill children - Демченко, Людмила Володимирівна (Slobozhanskyi Herald of Science and Sport, 2016)
Demchenko L. Purpose: to establish the degree of parental awareness of using means of physical rehabilitation on the frequently ill children with acute respiratory viral infections. Material & Methods: analysis of scientific and methodological literature, surveys and questionnaires. Results: the research involved 54 families with the frequently ill children. The paper characterizes and establishes the degree of parental awareness in the sphere of physical rehabilitation of the frequently ill children, determines the level of parental interest in cooperation, presents the plan of seminars with parents. Conclusions: increasing the degree of parental awareness by studying and explaining is a prerequisite to achieve high effectiveness in health recovery process of the frequently ill children.